Experimental investigation on possible dependence of plastic zone size on specimen geometry - K. K. Ray; B. Maiti; S. K. Kudari (Fracture and Structural Integrity)
In this investigation the extent of the plastic zone size ahead of a crack-tip in single edge notched tension (SENT), compact tension (CT) specimens has been examined experimentally by micro-hardness technique and by elastic-plastic finite element analyses at different applied load levels. The magnitudes of the plastic zone size (PZS), rp ahead of crack-tip in the investigated specimens have been compared using normalized J-integral (J/aYS, where, a-crack length and YS-yield stress of the material). The results show the dependence of PZS on specimen geometry due to varied in-plane crack-tip constraint. The results also demonstrate that the existing analytical models do not explain the experimental results of PZS satisfactorily.